2012
DOI: 10.1007/jhep04(2012)019
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum stability, neutrinos, and dark matter

Abstract: Motivated by the discovery hint of the Standard Model (SM) Higgs mass around 125 GeV at the LHC, we study the vacuum stability and perturbativity bounds on Higgs scalar of the SM extensions including neutrinos and dark matter (DM). Guided by the SM gauge symmetry and the minimal changes in the SM Higgs potential we consider two extensions of neutrino sector (Type-I and Type-III seesaw mechanisms) and DM sector (a real scalar singlet (darkon) and minimal dark matter (MDM)) respectively. The darkon contributes p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 55 publications
2
59
0
Order By: Relevance
“…On the other hand, M h = 125.66±0. 34 GeV lies well within the parameter window in which the SM can be extrapolated all the way up to the Planck mass M Pl , with no problem of consistency other than remaining in the dark about naturalness. Remarkably, in the context of the SM the measured value of M h is special because it corresponds to a near-critical situation in which the Higgs vacuum does not reside in the configuration of minimal energy, but in a metastable state close to a phase transition [8] (for earlier considerations see ; for related studies see ).…”
Section: Introductionmentioning
confidence: 65%
“…On the other hand, M h = 125.66±0. 34 GeV lies well within the parameter window in which the SM can be extrapolated all the way up to the Planck mass M Pl , with no problem of consistency other than remaining in the dark about naturalness. Remarkably, in the context of the SM the measured value of M h is special because it corresponds to a near-critical situation in which the Higgs vacuum does not reside in the configuration of minimal energy, but in a metastable state close to a phase transition [8] (for earlier considerations see ; for related studies see ).…”
Section: Introductionmentioning
confidence: 65%
“…In our simple model we couple the additional scalar to the Standard Model through a Higgs portal [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91] added to the effective potential of eq. (2.6),…”
Section: Jhep04(2015)022mentioning
confidence: 99%
“…Writing the RG equations for the top quark, neutrino, Higgs and singlet quartic couplings we have [8][9][10][11][12] …”
Section: Running the Initial Conditions For The Model With Cutoff Funmentioning
confidence: 99%
“…The potential was derived and given in full detail in our earlier work [2]. Recently and in more than one work [3][4][5][6], it was shown that adding a singlet (real or complex) scalar field, whose potential mixes with the Higgs field, has important consequences. It turned out that the RG equations of the combined Higgs-singlet system solves the stabilization problem faced with a light Higgs field of the order of 125 Gev avoiding making the Higgs quartic coupling negative at very high energies.…”
Section: Jhep09(2012)104mentioning
confidence: 99%